Guidelines for Promoting the Quality of Primary Teachers at the Digital Age - Atchariyakiat, Nawaporn; Sothayapetch, Pavinee (Journal of Dhamma for Life, 2025)
This study aims to: 1) investigate the essential needs regarding the quality of primary school teachers in the digital age, and 2) propose strategies to enhance the quality of primary school teachers in the digital age. A mixed-methods research approach was employed, which consisted of two phases. In Phase 1, a survey was conducted to examine the essential needs related to the quality of primary school teachers in the digital age. The sample consisted of primary school teachers selected through stratified random sampling, resulting in a total sample size of 486 teachers. The data were analyzed to assess the essential needs for teacher development. In Phase 2, expert group discussions were held with 6 experts to synthesize strategies for improving the quality of primary school teachers in the digital age. The content analysis method was used to derive these strategies. The findings revealed that: 1) Primary school teachers showed essential needs for development in 7 key areas and 2) The proposed strategies for promoting teacher quality in the digital age included: fostering collaboration with all stakeholders, including parents and other agencies, focusing on individual learner analysis before designing instructional approaches, promoting the use of technology in teaching, and ensuring safety by monitoring potential risks associated with technology use. Additionally, the concept of a digital professional learning community was recommended to encourage a growth mindset among teachers. School administrators and educational authorities were also advised to recognize and reward teachers with exceptional and proven performance to further motivate the enhancement of teacher quality in the digital age.